The Role of the Menara Kudus Mosque in Promoting Religious Moderation in Society - Nur Ahmad; Hidayati, Nurul (Journal of Community Development and Disaster Management, 2025)
Research on religious tourism in Indonesia has predominantly focused on socio-economic impacts and destination governance. However, scholarly attention that links religious tourism management with the cultivation of religious moderation values remains relatively limited, particularly in historically significant religious sites such as the Menara Kudus Mosque complex. This study seeks to explore the management practices of religious tourism at the Menara Kudus Mosque and to examine how these practices contribute to fostering values of religious moderation among pilgrims and the surrounding community. This research employs a qualitative descriptive method, with the study conducted in the Menara Kudus Mosque complex, including the Menara Kudus area and the tomb of Sunan Kudus. The participants of this study consist of foundation administrators, religious leaders, local traders, pilgrims, and residents living around the site. Data collection was carried out through in-depth interviews, direct observation in the field, and documentation. The collected data were then analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. To ensure the credibility of the findings, data validity was examined through source triangulation and methodological triangulation. The findings indicate that religious tourism management at the Menara Kudus Mosque is implemented through a balanced integration of sacred religious functions, preservation of cultural heritage, and local economic activities. This integrated management approach creates a conducive environment for spiritual reflection while maintaining social harmony in the surrounding community. Furthermore, the values of religious moderation are reflected in several aspects, including the architectural acculturation of the mosque complex, the management of religious traditions, and socio-religious practices that promote tolerance and respect for diversity. These values are closely connected to the historical legacy of Sunan Kudus' preaching, which emphasized cultural accommodation and harmonious coexistence. This study highlights the strategic role of religious tourism in supporting sustainable religious moderation education. In addition, the findings may serve as a reference for tourism managers and policy makers in formulating religious destination management strategies that uphold religious values while also contributing to community welfare.